2002
DOI: 10.1016/s0024-4937(02)00200-1
|View full text |Cite
|
Sign up to set email alerts
|

Triassic blueschists and eclogites from northwest Turkey: vestiges of the Paleo-Tethyan subduction

Abstract: Triassic eclogite and blueschist facies rocks occur as a thrust sheet, 25-km long and over 2-km thick, in an Eocene fold-andthrust belt in northwest Turkey along the İzmir -Ankara suture. The thrust sheet consists mainly of metabasites with minor marble, phyllite and metachert, and rare lenses of serpentinite. The common blueschist facies mineral assemblage in the metabasites is sodic amphibole + epidote + albite + chlorite + phengite F garnet. Sodic amphibole commonly shows replacement by barroisite, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 64 publications
3
107
0
1
Order By: Relevance
“…In Söğüt region, K-Ar biotite and Pb-Pb zircon evaporation ages are~290 Ma (Çoğulu & Krummenacher, 1967;Çoğulu, Delaloye & Chessex, 1965), and one Ar-Ar amphibole age is 272 ± 2 Ma (Okay, Monod & Monié, 2002). However, the granitoid ages in these regions are known to be Carboniferous, hence younger ages from the granitoids should represent later metamorphic (heating?)…”
Section: The Variscan Metamorphism In the Sakarya Zonementioning
confidence: 99%
“…In Söğüt region, K-Ar biotite and Pb-Pb zircon evaporation ages are~290 Ma (Çoğulu & Krummenacher, 1967;Çoğulu, Delaloye & Chessex, 1965), and one Ar-Ar amphibole age is 272 ± 2 Ma (Okay, Monod & Monié, 2002). However, the granitoid ages in these regions are known to be Carboniferous, hence younger ages from the granitoids should represent later metamorphic (heating?)…”
Section: The Variscan Metamorphism In the Sakarya Zonementioning
confidence: 99%
“…The high pressure metamorphism of some Neotethyan ophiolites along the İzmir-Ankara-Erzincan suture zone supports this suggestion. The oldest radiometric ages from the high pressure metamorphic rocks associated with the Neotethyan ophiolite to the north of Eskişehir town range between 204 and 215 Ma, (Okay et al 2002). The average ages (204)(205) indicate that the subduction of the Neotethyan oceanic lithosphere began 30-40My after the rifting of the Neotethyan Ocean.…”
Section: Discussion and Geodynamical Evolutionmentioning
confidence: 99%
“…During Mesozoic times, the Tethyan Ocean formed a gulf towards the west between the two continents. Various hypotheses have been suggested on the shape and the evolution of the Tethyan embayment including single or multi-branched Tethys; opening and closure times of the Neotethyan Ocean; as well as the time and the polarity of the Tethyan subduction (Ricou et al 1975;Bijou-Duval et al 1977;Şengör & Yılmaz 1981;Knipper et al 1986;Okay & Tüysüz 1999;Stampfli 2000;Okay et al 2002;Robertson 2002;Çakır 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Aral's work in the Biga Peninsula showed that the Karakaya Complex has a lower unit composed predominantly of metabasites, representing an accreted Permo-Triassic oceanic plateau or large number of oceanic islands, which is overlain by chaotically deformed volcanic and sedimentary rocks of the Upper Karakaya Complex. His discovery of latest Triassic eclogites and blueschists in the Lower Karakaya Complex in north-west Turkey (Okay & Monié, 1997;Okay, Monod, & Monié, 2002) showed convincingly a subduction rather than rift origin of the Karakaya Complex. The presence of Permo-Carboniferous limestone blocks were long known in the Upper Karakaya Complex.…”
Section: Prefacementioning
confidence: 99%